2003
DOI: 10.1210/jc.2003-030233
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 Receptor Gene: Case-Control Study and Transmission Disequilibrium Test Confirm that Functionally Relevant Mutations Are Compatible with a Major Gene Effect for Extreme Obesity

Abstract: We initially performed a mutation screen of the coding region of the MC4R in 808 extremely obese children and adolescents and 327 underweight or normal-weight controls allowing for a case-control study. A total of 16 different missense, nonsense, and frameshift mutations were found in the obese study group; five of these have not been observed previously. In vitro assays revealed that nine [the haplotype (Y35X; D37V) was counted as one mutation] of the 16 mutations led to impaired cAMP responses, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
184
3
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(209 citation statements)
references
References 29 publications
11
184
3
11
Order By: Relevance
“…It is thought to explain 2-6% of extremely obese childhood and adolescent cases (Farooqi et al, 2003;Hinney et al, 2003Hinney et al, , 2006Santini et al, 2004;Wang & Tao, 2011). The MC4R is a membrane-bound G-protein-coupled receptor that activates adenylate cyclase; in response to the α-melanocyte-stimulating hormone (α-MSH), MC4R induces production of cAMP (Stutzmann et al, 2008;Caruso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought to explain 2-6% of extremely obese childhood and adolescent cases (Farooqi et al, 2003;Hinney et al, 2003Hinney et al, , 2006Santini et al, 2004;Wang & Tao, 2011). The MC4R is a membrane-bound G-protein-coupled receptor that activates adenylate cyclase; in response to the α-melanocyte-stimulating hormone (α-MSH), MC4R induces production of cAMP (Stutzmann et al, 2008;Caruso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various missense, nonsense and frameshift MC4R mutations have been described (Human Mutation Database, HGMD; http://www.hgmd.cf.ac.uk) in a wide patient series with distinct ancestral origins. Currently, the clinical genotype-phenotype relationships in adult MC4R mutation carriers constitute an essential objective to define and corroborate the severity of each functional alteration (Hinney et al, 2003(Hinney et al, , 2006Lubrano-Berthelier et al, 2006;Wang & Tao, 2011). To date, more than 150 different MC4R mutations, mostly leading to a reduced function, have been detected in obese individuals (Hinney et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…35 However, functional analysis of all three polymorphisms did not indicate a difference to wild type MC4R. 14,15,18,34 …”
Section: Discussionmentioning
confidence: 94%
“…A number of groups detected mutations at high frequency among obese patients. [12][13][14][15][19][20][21][22][23][24] As shown in Table 3, the frequency of pathogenic MC4R mutations in these populations ranged from 2.5% 21 to as high as 6.3%. 12 These studies clearly focused on children with severe obesity and adults with reported early onset of obesity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation